A new diplodocine sauropod from the Morrison Formation, Wyoming, USA - van der Linden, Tom T.P. (2024)
The Morrison Formation of the western United States is well-known for its high diversity of sauropod dinosaurs. The Howe-Stephens Quarry in northern Wyoming is one of several quarries which has yielded several associated to completely articulated dinosaur specimens, among which a semi-articulated diplodocid specimen, MAB011899, which was excavated in 1993. This diplodocid specimen is represented by posterior cervical, dorsal, sacral, and anterior caudal vertebrae, multiple thoracic ribs, two chevrons, a left coracoid, a left ilium, both pubes and ischia, a left femur, a left tibia, and a left fibula. Through comparative anatomy, we interpret this specimen as a new species of diplodocine sauropod, Ardetosaurus viator gen. et sp. nov. Unambigu-ous autapomorphies include paired accessory laminae in the spinoprezygapophyseal fossae of posterior cervical and anterior dorsal vertebrae, bifurcating anterior centrodi-apophyseal laminae in the anterior dorsal vertebrae, fossae present in the centropost-zygapophyseal laminae of the second dorsal vertebra, a low vertebral height/centrum length ratio of the posterior dorsal vertebrae and reduced to absent centroprezyga-pophyseal laminae in the anterior caudal vertebrae. Local autapomorphic features include single centroprezygapophyseal laminae in the posterior cervical vertebrae and a highly elliptical cross-section of the femoral midshaft. Ardetosaurus viator is the first skeletally mature sauropod specimen described from the Howe-Stephens Quarry. This specimen provides insight into serial variation of vertebral laminae and laminar transitions. Finally, the peculiar morphology of the-often not preserved-first chevron is described in detail, and its possible use in studying sexual dimorphism in sauropods is discussed.